2006
DOI: 10.3960/jslrt.46.1
|View full text |Cite
|
Sign up to set email alerts
|

Senile Epstein-Barr Virus-Associated B-Cell Lymphoproliferative Disorders: a Mini Review

Abstract: Epstein-Barr virus (EBV) is associated with a number of malignant lymphomas, including Burkitt lymphomas, Hodgkin lymphomas (HLS), immunodeficiency-associated lymphoproliferative disorders (LPDs), and subset of diffuse large B-cell lymphomas. We have recently identified a series of elderly patients afflicted with EBV-associated (EBV-positive) B-cell LPDs in the absence of predisposing immunodeficiencies ; we have named these neoplasms "senile" EBV + B-cell LPDs. The large series of patients with this disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 14 publications
6
68
2
1
Order By: Relevance
“…Moreover, in recent years, it has been proposed that defective immune surveillance for EBV may develop late in life and be associated with the development of EBV positive B-cell lymphoproliferative disorder. 47 This defective immune surveillance for EBV is associated with immunological deterioration as a result of aging process, 3,[48][49][50] and explains the correlation between an increased incidence of this lymphoma type together with the increased age of the patients found in the Eastern series. Surprisingly, we did not observe major differences linked with age of the relative numbers of any T-cell population analyzed (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in recent years, it has been proposed that defective immune surveillance for EBV may develop late in life and be associated with the development of EBV positive B-cell lymphoproliferative disorder. 47 This defective immune surveillance for EBV is associated with immunological deterioration as a result of aging process, 3,[48][49][50] and explains the correlation between an increased incidence of this lymphoma type together with the increased age of the patients found in the Eastern series. Surprisingly, we did not observe major differences linked with age of the relative numbers of any T-cell population analyzed (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1 This defective immune surveillance for EBV is associated with immunological deterioration as a result of aging [3][4][5] and explains the correlation between the increased incidence of this lymphoma type and the increased age of the patients found in the Eastern series. However, the definitional cutoff of 50 years proposed by the WHO is arbitrary, 2,4 and cases below the age of 50 years can be found, provided an undiagnosed underlying immunodeficiency has been ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…8,13,14 Published studies of clinical series have identified a high risk of treatment failure in these patients. 5,8 Among the clinical factors that have an impact on patient outcome, only B symptoms and an age of 70 þ years are independently predictive of survival, while the International Prognostic Index score did not seem to separate different risk groups as in conventional EBVnegative diffuse large B-cell lymphomas. 9 Among the biological features of the tumors that might influence patient survival, it seems clear that EBV positivity is a risk factor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The entity was further subdivided into a polymorphic category (broad range of B-cell differentiation in an inflammatory background) and a large cell category (monomorphic large cells) [69]. EBV was detected in all cases; and a latency III program was most often expressed, although some cases lacked EBNA2 expression (latency II) [69,70]. The variable presence of EBNA2 expression may be attributed to the variable degrees of immune surveillance in aging individuals.…”
Section: Ebv-associated B-cell Lymphoproliferative Disordersmentioning
confidence: 99%